Design Of CMOS Ultra High Frequency Radio Frequency Identification Analogue Front End Using Dynamic Threshold Mosfet Techniques - Teh, Ying Khai (2008)
The application of high frequency (UHF) radio frequency identification (RFID) has been gaining momentum since the ratification of EPC Class 1 Gen 2 ( EPC CIG2, also known as ISO 18000-6C) protocol. The limited availability of Schottky barrier diode (SBD) has stimulated the investigation of alternate circuit solutions to fabricate UHF RFID chips of comparable performance using typical CMOS processes.